1988
DOI: 10.1063/1.339926
|View full text |Cite
|
Sign up to set email alerts
|

Transient boron diffusion in ion-implanted crystalline and amorphous silicon

Abstract: Boron diffusion in ion-implanted and annealed single-crystal and amorphized Si is compared to determine the effect of amorphization on the initial transient boron motion reported for single crystal. The boron was implanted at 20 keV and at doses of 1×1015 and 3×1015cm−2. The Si was either preamorphized or postamorphized to a depth of 320 nm by implantation of Si ions at three different energies. In the amorphized samples the entire boron profile was always contained within this distance. The samples were annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
4

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(52 citation statements)
references
References 29 publications
6
42
4
Order By: Relevance
“…Others have reported similar results. 4 In order to understand the correlation of TED with defects arising from annealing following B ϩ damage, a number of studies have been conducted on the defect formation processes. [5][6][7][8][9][10] These studies have indicated that TED of B ϩ -implanted Si occurs by the pairing of B with Si self-interstitials.…”
mentioning
confidence: 99%
“…Others have reported similar results. 4 In order to understand the correlation of TED with defects arising from annealing following B ϩ damage, a number of studies have been conducted on the defect formation processes. [5][6][7][8][9][10] These studies have indicated that TED of B ϩ -implanted Si occurs by the pairing of B with Si self-interstitials.…”
mentioning
confidence: 99%
“…In addition, junction degradation at ST of 900 "C was present for the 750 and 900 "C activation, whereas no high-temperature deterioration was found for the 1000 "C activation. Previously, anomalous dopant diffusion was reported to occur during annealing due to interstitial defects [7]. Moreover, DLTS analyses of the silicided junctions indicated a deep level of about 0.6 eV which is close to the trap level of CO in Si.…”
Section: Resultsmentioning
confidence: 96%
“…3 shows the boron depth profiles for the ITP and the Ni/ITP samples, respectively, implanted at 25 keV and annealed at 700 C. The simultaneous silicidation and junction formation would considerably drive-in the boron dopant and cause excellent junction in the Si substrate. While annealing, the diffusion of boron would be enhanced due to Si interstitial [11]. And, silicidation would also enhance the dopant diffusion [9], [10].…”
Section: Resultsmentioning
confidence: 97%